The Binga outreach: a critical reflection on the Reformed Church in Zimbabwe's cross-cultural ministry - Munikwa, Christopher; Hendriks, H. Jurgens (Missionalia: Southern African Journal of Missiology, 2013)
This article describes the first cross-cultural outreach of the Reformed Church in Zambia (RCZ) to a non-Shona speaking group. This Church founded preaching posts and, eventually, a congregation among the Tonga people living in the Binga area on the southern side of the Zambezi River / Kariba Lake. These people, of a unique culture, were displaced from their land, causing great suffering, when the dam was built and the lake formed. They received very little compensation if any. Other tribes looked down on the Tonga people. In the nineties, University students initiated an evangelism outreach. This article describes the events, relates something about the Tonga people, and deals with the RCZs discovery that they were defaulting to the missionary methods of the Dutch Reformed Church (DRC) that founded their Church more than a hundred years earlier. This realization led to the question how they should go about reaching out to different cultural groups of people.